Pengaruh Kompensasi, Disiplin Kerja, Dan Motivasi Kerja Terhadap Kinerja Pegawai PT. Pertamina Retail - Linda Ratna Fitria Cahyani; Asmirin Noor; Emmywati Emmywati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to find out whether compensation, motivation and work discipline influence employee performance at PT Pertamina Retail. This type of research is quantitative. The population studied in this research were all employees at PT Pertamina Retail. The number of samples in this study was 50 respondents. The sample collection technique in this research was carried out using saturated sampling. The data collection technique used in this research was a questionnaire distributed to all PT Pertamina Retail employees. The data analysis technique used in this research is multiple linear regression analysis using SPSS (Statistical Product and Services Solution) software version 29.0. The research results show that compensation, motivation and work discipline partially and simultaneously have a significant effect on employee performance at PT Pertamina Retail. The R Square value of the reward and punishment variables influencing employee performance is 35.5%.